Republics at War, 1776-1840 Revolutions, Conflicts, and Geopolitics in Europe and the Atlantic World - Serna, P.; Francesco, A. De.; Miller, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This collection probes the troubling connections between war and republic during Revolutionary era, 1776-1840. It presents the work of an international team of scholars, some of them in English for the first time.
Keywords: Military history; Social history; History, Modern; World history; Europe—History.; Imperialism; History of Military; Social History; Modern History; World History, Global and Transnational History; European History; Imperialism and Colonialism